VITAMIN DEFICIENCY AND INSULIN RESISTANCE IN NONDIABETIC OBESE PATIENTS - Cigerli, O. (Acta Endocrinol (Buchar), 2016)
OBJECTIVE: Obese people may have nutritional deficiencies, although they are exposed to excessive food intake. We aim to assess relationship of vitamin D, B12, and folic acid levels and dietary vitamin intake and insulin resistance in obese people. DESIGN: This case-control study was performed at the obesity outpatient clinics between March 2014 and April 2015. SUBJECTS AND METHODS: We included 304 non-diabetic obese subjects in patient group and 150 normal weight individuals in control group. Patients were questioned in detail about their food intake. RESULTS: Mean age of obese patients was 37.3±10.1 years, the mean duration of obesity was 7.9±5.4 years, and the percentage of female patients was 65.8%. Mean vitamin D, B12, and folic acid levels were significantly lower in patients than in controls. Vitamin D deficiency (<20 ng/mL) in 69.7%, vitamin B12 deficiency (<200 pg/mL) in 13.5%, and folic acid deficiency (<4 ng/mL) was found in 14.2% of the patients. BMI negatively correlated with vitamin D, B12, and folic acid levels. B12 levels negatively correlated with duration of obesity. Insulin resistance was found in 55.9% of patients and HOMA-IR levels negatively correlated with vitamin D and B12 levels. While dietary vitamin D and folic acid intakes were inadequate in all of patients, only 28.3% of patients had inadequate vitamin B12 intake. There was no relation between vitamin levels and dietary vitamin intakes. CONCLUSIONS: The study reveals that vitamin D, B12, and folic acid levels were low and poor vitamin D and B12 status were associated with insulin resistance in nondiabetic obese patients.